2012
DOI: 10.1021/jp2094559
|View full text |Cite
|
Sign up to set email alerts
|

Car–Parrinello Simulation of the Vibrational Spectrum of a Medium Strong Hydrogen Bond by Two-Dimensional Quantization of the Nuclear Motion: Application to 2-Hydroxy-5-nitrobenzamide

Abstract: The nature of medium strong intra- and intermolecular hydrogen bonding in 2-hydroxy-5-nitrobenzamide in the crystal phase was examined by infrared spectroscopy and Car-Parrinello molecular dynamics simulation. The focal point of our study was the part of the infrared spectra associated with the O-H and N-H stretching modes that are very sensitive to the strength of hydrogen bonding. For spectra calculations we used an isolated dimer and the fully periodic crystal environment. We calculated the spectra by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…It was shown previously that this choice is better than more sophisticated elongation because this treatment give results more similar to 2D example. 51 This agrees with our predictions from calculated geometry parameters (Table 1). Only the second hydrogen bond HB2 is weaker in molecule II.…”
Section: Simulation Of the O-h Stretching Bandshapesupporting
confidence: 91%
“…It was shown previously that this choice is better than more sophisticated elongation because this treatment give results more similar to 2D example. 51 This agrees with our predictions from calculated geometry parameters (Table 1). Only the second hydrogen bond HB2 is weaker in molecule II.…”
Section: Simulation Of the O-h Stretching Bandshapesupporting
confidence: 91%
“…These bonds are characterized by essential mechanical and electric anharmonicity . Accurate treatment of systems with relatively short (strong) H‐bonds requires the use of advanced methods that are cumbersome and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the snapshot methodology has become a powerful approach for analyzing the strength of HB interactions . First, approaches based on MD simulations have considered effects neglected in the static results, such as the thermal modes of nuclei .…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that the quantization of motion can provide valuable information about the properties of the systems in different phases . Especially, it has been demonstrated that quantization treatment is useful for understanding HB interactions …”
Section: Introductionmentioning
confidence: 99%